2D‐(Alumino)Silicate‐Noble Clathrates: Ionization‐Facilitated Formation of 2D (Alumino)Silicate–Noble Gas Clathrate Compounds (Adv. Funct. Mater. 20/2019). (14th May 2019) - Zhong, Jian‐Qiang; Wang, Mengen; Akter, Nusnin; Kestell, John D.; Niu, Tianchao; Boscoboinik, Alejandro M.; Kim, Taejin; Stacchiola, Dario J.; Wu, Qin; Lu, Deyu; Boscoboinik, Jorge Anibal
Abstract : In article number1806583, Deyu Lu, Jorge Anibal Boscoboinik, and co‐workers develop two‐dimensional arrays of hexagonal prism nano‐cages trapping single atoms of noble gases argon, krypton, and xenon. These atoms are stable in the cages at elevated temperatures.